Edukasi Kecemasan dan Latihan Brain Gym Pada Penderita Hipertensi - Arif Hendra Kusuma; Siti Azizah (JPS : Jurnal Pengabdian Serulingmas, 2022)
ABSTRACTHypertension disease can develop for many years without symptoms and without any complaints. This condition causes anxiety in hypertension patients. A person's concern about the emergence of a new problem that exists in hypertension will cause emotional mental disorders or feelings that we often encounter one of which is anxiety. Management of anxiety sufferers with hypertension is needed to maintain their quality of life. The need for a complementary or complementary therapy in addition to drug therapy consumed by people with hypertension. One of the complementary therapies that can be used is Brain Gym. Brain Gym is not intended to replace drug therapy that has been given to people with hypertension, but only helps to reduce the patient's dependence on drugs. The purpose of this activity is to increase public knowledge about anxiety in people with hypertension and increase people's skills on how to overcome anxiety with the brain gym. The target in this activity is people with hypertension who are in Kalijaran Village which amounts to 11 people. The results of the activity showed an increase in the knowledge of educational participants about anxiety and improved skills in managing anxiety with brain gym exercises in people with hypertension in Kalijaran Village, Maos Subdistrict